Pleuropulmonary solitary fibrous tumour with paraneoplastic syndrome - Zainulabid, Ummu Afeera; Abdul Razak, Megat Razeem; Md Salleh, Nor Hafliza; Othman, Noriah; Mohamed, Dahlia (International Journal of Human and Health Sciences, 2021)
The pleuropulmonary solitary fibrous tumour (SFT) is a rare type of tumour. This paper outlined a 63-year-old female who came to the hospital with two weeks history of chronic cough, shortness of breath, and hypoglycemia. Contrast-Enhanced CT Thorax showed a huge heterogeneously-enhancing mass occupying the right hemithorax. US-guided biopsy followed by histological examination showed the features of an SFT. In view of the association between pleuropulmonary SFT and hypoglycaemia, the patient was highly likely to be suffering from a paraneoplastic syndrome known as Doege-Potter Syndrome.